MANEJO SANITÁRIO E BEM- ESTAR NA CRIAÇÃO DE LEITÕES (REMUNOM, 2023)
Pig farming has been a practice present in humanity for more than seven millennia, with mass production and presence in the global economy since the mid-20th century. It is a rapidly expanding area of ​​livestock farming, with pork being one of the most consumed in the world and Brazil as its fourth largest producer. In the country, domestic consumption is three times greater than what is produced for export. In any case, this increase in demand for this type of protein has also raised questions related to the production methods of this industry. In the present work, aspects of health management and animal welfare (BEA) are addressed, whose boundaries are more methodological than practical, as it is not possible to exist animal welfare, which comprises aspects related to the life and death of these individuals. about hunger and thirst, fear and anguish, discomfort, pain and/or injury, and freedom to express their natural behaviors, without these individuals being in an environment that are also from a health point of view. When producers are able to comply with these aspects, all actors involved in the swine chain benefit, as there is a higher quality of life for the animals and greater safety.